2011
DOI: 10.2147/ijwh.s26094
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gestational diabetes and associated maternal and neonatal complications in a fast-developing community: global comparisons

Abstract: BackgroundThe prevalence of gestational diabetes (GDM) is increasing all over the world. Hence, the impact of GDM on maternal and infant health is an important topic of research. No study has been conducted in Qatar to evaluate the outcome of pregnancies complicated by diabetes mellitus.ObjectiveThe aim of the study was to determine the prevalence of GDM, compare the maternal–neonatal complications among women with GDM and non-GDM pregnant women, and investigate the risk factors and potential outcomes associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
126
7
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(160 citation statements)
references
References 26 publications
19
126
7
8
Order By: Relevance
“…Obesity emerged as an essential risk factor for subsequent GDM. The advanced maternal age, low monthly income, family history of advanced maternal age, low monthly income, family history of diabetes and obesity were the main significant risk factors for GDM [28], which are similar to the results of our study. However our study did not assess the prevalence of GDM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Obesity emerged as an essential risk factor for subsequent GDM. The advanced maternal age, low monthly income, family history of advanced maternal age, low monthly income, family history of diabetes and obesity were the main significant risk factors for GDM [28], which are similar to the results of our study. However our study did not assess the prevalence of GDM.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, it was found that, the women who developed GDM had significantly more number of children (Nullipara were 85 cases (44.5%) of total sample size and no one had GD with Mean+SD 97.61+13.20, 1-2 children were 73 cases of total sample size, 72 cases (37.7%) were normal and 1 case (11.1%) had GD with Mean+SD 98.23+16.87, 3 or more were 42 cases of total sample size, 38 cases (17.8%) were normal and 8 cases (88.9%) had GD with Mean+SD 119.62+40.08) with p-value 0.000, also we found a relationship between elevated serum uric acid level and the development of preeclampsia (18 cases developed preeclampsia, 15 cases with normal serum uric acid (83.3%) and 3 cases had elevated serum uric acid (16.7%)) and (182 did not develop preeclampsia, 179 cases with normal serum uric acid (89.4%) and 3 cases had elevated serum uric acid (1.6%)) with p-value 0.000 this agrees with Bener et al [28], in a prospective cohort study carried out at the antenatal clinics of the Women's Hospital Qatar. 2056 pregnant women were surveyed during the period from January 2010 to April 2011.…”
Section: Discussionsupporting
confidence: 86%
“…To the best of our knowledge, this is the first study reporting the effect of vitamin D supplementation on pregnancy outcomes of pregnant women with GDM. Gestational diabetes is linked with several adverse pregnancy outcomes in maternal, offspring's, as well as later in their lives [8,[23][24][25]. The current study showed that taking vitamin D supplements in pregnant women with GDM resulted in decreased polyhydramnios, but did not affect rate of cesarean section, need to commence insulin therapy after intervention and preterm delivery.…”
mentioning
confidence: 53%
“…O DMG é um bom exemplo para se analisar a pesquisa translacional visto que é uma das principais causas de morbidade e mortalidade perinatal, bem como da repercussão a longo prazo na vida da mulher (9)(10)(11)(12). A intrincada relação entre o que se observa na prática da atividade clínica e o que se obtém de resultados em pesquisa clínica e de investigação em ciência básica deve ser organizada e analisada dentro de um contexto único que, nos dias de hoje, é denominado "Pesquisa Translacional".…”
Section: Introductionunclassified